Humoral and cellular immune memory response 12 years following single dose vaccination against hepatitis A in Argentinian children. Issue 1 (3rd January 2022) - Urueña, A.; Badano, M.N.; Baré, P.; González, J.; Vicentín, R.; Calli, R.; Cañero-Velasco, M.C.; Fink, S.; Vizzotti, C.
Highlights: HAV booster vaccination elicited an adequate humoral memory response in most individuals. HAV-specific memory T-cells response was observed independently of anti-HAV antibodies titers. Long-term humoral and cellular immunity demonstrated here, supports the single-dose HAV strategy. Abstract: Infants' universal hepatitis A virus (HAV) single-dose vaccination has been highly effective for controlling HAV infection in Argentina, and in other Latin-American countries that adopted that strategy. Although antibodies wane over time, this has not been associated with HAV outbreaks or breakthrough infections, suggesting a relevant role for memory immunity. This study assessed long term humoral and cellular immune memory response after an average of 12 years follow-up of HAV single-dose vaccination. We selected 81 HAV-single dose vaccinated individuals from a 2015 study, including 54 with unprotective (UAL) and 27 with protective antibody levels (PAL) against HAV. Humoral memory response was assessed by measuring anti-HAV antibody titers at admission in both groups, and 30 days after a booster dose in the UAL group. Flow cytometry analysis of peripheral blood mononuclear cell samples stimulated with HAV antigen was performed in 47/81 individuals (21 with PAL, 26 with UAL) to identify activated CD4 + memory T cells or CD8 + memory T cells. The results showed that 48/52 (92%) individuals from UAL group who completed follow up reached protective levels after booster dose. In the PAL group, anti-HAV Abs waned in 2/27 (7%) individuals lacking seroprotection, while in 25/27 (93%) Abs remained >10 mUI/mL. HAV-specific memory CD4 + T cells were detected in 25/47 (53.2%) subjects while HAV-specific memory CD8 + T cells were observed in 16/47 (34.04%) individuals. HAV-specific memory CD4 + and CD8 + T cell responses were detected in 11/21 (52.4%) and in 9/21 (42.9%) subjects with PAL and in 14/26 (53.8%) and in 7/26 (26.9%) individuals with UAL, showing that the presence of memory T-cells was independent of the level or presence of anti-HAV antibodies. Long-term immunity demonstrated in the present work, including or not antibody persistence, suggests that individuals with waned Ab titers may still be protected and supports the single-dose HAV strategy.